Bio-inspired vertically aligned polyaniline nanofiber layers enabling extremely high-efficiency solar membrane distillation for water purification. Issue 17 (27th April 2021) - Peng, Yubing; Wang, Yunjie; Li, Wenwei; Jin, Jian
Abstract : A bio-inspired PANI nanofiber layer was fabricated on the surface of a hydrophobic PVDF microfiltration membrane for solar-driven distillation. This membrane possesses high solar energy-to-collected water efficiency for freshwater production under one sun irradiation. Abstract : Solar-driven desalination technologies, including solar steam generation and solar-driven membrane distillation (SDMD), provide a sustainable avenue to generate clean water from wastewater and seawater. In particular, SDMD is attractive due to efficient vapor collection and high-quality water production, but the limited solar energy-to-collected water efficiency is the major remaining barrier to its practical application. Inspired by the nanoscale anti-reflection structure on the surface of moth eyes, we report in this work a bio-inspired design of a photothermal membrane for SDMD, which is composed of a vertically-aligned polyaniline (PANI) nanofiber layer on the surface of a hydrophobic polyvinylidene fluoride (PVDF) microfiltration membrane. The superb light-trapping effect stemming from the vertically-aligned PANI nanofiber layer offers the photothermal membrane a high light absorption of up to 95% in the UV-visible range of the solar spectrum. The photothermal membrane thereby shows outstanding performance for direct contact SDMD with a distillation flux of 1.09 kg m −2 h −1 and a corresponding solar energy-to-collected water efficiency as high as 74.15% under one sun irradiation, and outperforms state-of-the-art direct contact SDMD photothermal membranes without pre-heating the feed reported so far. This work provides a simple avenue to fabricate advanced photothermal membranes with excellent performance for SDMD.